(untitled) (Research, Society and Development, 2021)
Objective: to identify scientific production or the use of therapeutic letters as a technology that facilitates communication between the nursing team and the patient. Methodology: this is a qualitative approach research of the integrative literature review type, carried out between December 2020 and January 2021. Results: search in Cinahl, Medline and Scopus databases, selected by 9 articles to Compose the final sample of this review. Conclusion: it is innovative and differential regarding the applicability of therapeutic letters for interpersonal relationships, or that it can demonstrate a more humanized care by the nursing team, motivating the patient to understand that the team is close to the entire recovery and treatment process, establishing a bond of trust, referral and counter-referral for assistance. There is little scientific production on the subject in question and, therefore, there is little scientific basis for this work, so it is necessary to either encourage these subjects referenced or as holistic human beings.